WORK-FAMILY CONFLICTS AND COPING MECHANISMS - Dilly, Anita (Hibualamo : Seri Ilmu-Ilmu Sosial dan Kependidikan, 2017)
The purpose of this research is to find out how females cope and continue to work in the middle of their high-pressured jobs and how they face family-job conflicts in an organization that does not apply flexible working. This research uses a qualitative approach with in-depth interview method on 3 respondents in a banking organization. The research results reveal that when flexible working is not a viable solution in the middle of a job condition with high work pressures and loads, coping with household responsibilities is an individual mechanism to deal with job pressures. Being a social culture in an Asian society that is family-oriented makes it possible to cope with household obligations. There is the nuclear family, extended family, and job social environment which help employees neutralize their job stress. Flexible working is a solution at places which do not facilitate coping mechanisms. Applying a flexible working intervention can be implemented to assist employees to fulfill a work-life balance, reduce job stress, and improve employee commitment to continue working in an organization.